The Trillion-Dollar Question: How AI is Driving Healthcare Cost Reduction Through Data-Driven Analysis - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The global healthcare system faces a critical challenge: the relentless and often unsustainable rise in expenditure. As populations age and chronic diseases ...
Keywords: Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care; Precision Medicine